Investigation on the Role of Steel Slag Powder in Blended Cement Based on Quartz Powder as Reference - Wei He; Jihui Zhao; Gangqiang Yang (Advances in Civil Engineering)
To clarify the role of steel slag powder in blended cement, steel slag powders with different amounts and particle sizes were mixed into blended cement and the inert quartz powder was selected as the reference. The influences of steel slag powder with different amounts and particle sizes on the hydration and hardening properties of blended cement were studied from hydration heat, nonevaporable water content, porosity, hydration products, and strength. The results show that the influence coefficient of nonevaporable water content (ՓWn) of blended cement paste is in an exponential relationship with the amount of steel slag powder. Moreover, at a dosage of 30%, ՓWn of blended cement gradually decreases with the increase of steel slag particle size. Both the early and late compressive strengths of blended cement are in a binomial relationship with the amount of steel slag powder. The influence coefficient of steel slag powder on the compressive strength of blended cement is negative at the age of 3 days, whereas it is positive at the age of 28 days. The chemical filling effect of 30% steel slag powder with different particle sizes in the blended cement paste is very small, only 1.13%–5.06%. The hydration products of blended cement containing steel slag are mainly amorphous C-S-H gels and platy Ca(OH)2, and their density are consistent with the law of their porosity.